A Systematic Review Of Multi-Agent Systems And Mobile Edge Computing In Intelligent Transportation Systems - Mohamed, Hassan; Marouane, Hend; Fakhfakh, Ahmed (Journal of Soft Computing and Data Mining, 2025)
The Internet of Vehicles (IoV) can be identified as the most progressive evolutionary stage in the development of Intelligent Transportation Systems (ITS), being, in fact, the result of a merging of modern communication technologies with the traditional vehicle network. This review provides an in-depth survey of the current state of knowledge regarding Multi-Agent Systems (MAS) and Mobile Edge Computing (MEC) applications in Intelligent Transportation Systems. The review further explored the MEC and MAS mechanisms as technological solutions of modern times, as they enable real-time data processing and intelligent decision-making at the edge of the network. This analysis ascertains the gaps in the literature. Further, it explores the subject within the broader scholarship, thereby defining the study objectives in the arena of improving ITS through Internet of Vehicles (IoV) technologies.